Pattern thinking : a strategic shortcut - Slywotzky, Adrian J. (2000)
Describes the application of pattern thinking to strategy. Opines that patterns provide a powerful discipline to see order beneath the surface chaos. Notes that pattern thinking can help entrepreneurs, managers, investors, and key talent to anticipate the likely direction of changes even before they happen. Indicates that it reveals the economic meaning of these changes and provides tools to capitalize on them.